Edible Bird’s Nest Supplementation Improves Male Reproductive Parameters of Sprague Dawley Rat - Jaffar, Farah Hanan Fathihah; Osman, Khairul; Hui, Chua Kien; Zulkefli, Aini Farzana; Ibrahim, Siti Fatimah (Frontiers in Pharmacology, 2021)
Edible bird’s nest (EBN) is reported to have a positive in vitro proliferative effect and contain male reproductive hormones. Spermatogonia cells proliferate during spermatogenesis under male reproductive hormones stimulation that include testosterone, follicle-stimulating hormone (FSH), and luteinizing hormone (LH). Characterization of EBN through liquid chromatography-mass spectrometry (LCMS) has found testosterone as a base peak. Six types of amino acids, estradiol and sialic acid were among the major peaks that has have been characterized. Based on the presence of these reproductive components, this study evaluated different doses of EBN on sperm parameters and male reproductive hormones of Sprague Dawley rats. Sixteen Sprague Dawley rats at the age of eight weeks were randomly and equally divided into four groups, which are Control, 10 mg/kg BW/d, 50 mg/kg BW/d, and 250 mg/kg BW/d EBN group. The rats were fed with EBN enriched pellet daily and water ad-libitum. Rats were sacrificed and the organ was weighed for organ coefficients after eight weeks of treatment. Sperm concentration, percentage of sperm motility, and sperm viability were evaluated. Meanwhile, ELISA method was used to measure testosterone, FSH, and LH. Findings showed that there were no significant differences in organ coefficient between groups. Supplementation of 250 mg/kg BW/d EBN demonstrated a significant increase in sperm concentration, percentage of sperm motility as well as FSH and LH level compared to 10 mg/kg BW/d group. There was a dose-dependent increase in testosterone level but was not significant between groups. Based on these findings, EBN is concluded to have crucial effects on male reproductive parameters.